Experiência da mulher com câncer de boca em relação à radioterapia - Macedo, Dhiancarlo Rocha (2017)
Introduction: Radiation therapy is the primary treatment for mouth cancer. During the radiotherapy treatment in the region of head and neck can occur several adverse reactions that affect in a significant way the quality of life of the patients, repercussing detrimentally in personal, professional, social and affective life. Most studies with this group of people submitted to radiotherapy use quantitative methodology; few are those of qualitative approach. Qualitative research provides a direct and interactive contact between the researcher and the participant, making it possible to understand the course of illness and cancer treatment from the perspective of those who live the experience.Objectives: To understand and describe the experience of radiotherapy treatment from the perspective of women with oral cancer, aiming to identify the sense attributed by the participant to the radiotherapy treatment and their desires in relation to their own life after completion of cancer treatment. Methodology: This is an exploratory and explanatory study that used the qualitative methodology. The theoretical reference was Medical Anthropology and as a methodological course the ethnographic case study was used. Operation of the study: Data were collected using resources from ethnography. The interviews were audio-recorded and later transcribed, and the thematic analysis of the data was performed concomitantly. Results: Six thematic units were identified: the diagnosis, discovering the metastasis, the radiotherapy trajectory, the importance of the multiprofessional team, support networks and life after radiotherapy. Of the adverse reactions, odynophagia, dysgeugia and weight loss during radiotherapy were the ones that stood out the most, being causes of the social isolation adopted by the participant. The post-radiotherapy period had as its main complaint the muscular weakness and the anxiety for the recovery of the weight, accompanied by feeling of hope for the future. The sense attributed to radiotherapy was 'optimism and hope, despite social isolation'. Final considerations: There was no negative construct in the participant's experience with radiotherapy; hope for the future was maintained after the end of treatment; anxiety related to body weight recovery was reported as an established condition for normality. We suggest that other studies with a qualitative methodology be used to explore more broadly and deeply the aspects of the subject addressed, including with the relatives of the patient, thus providing expanded understanding for different contexts, as well as identifying and adopting strategies that aim to improve the service offered and consequently improvement in the quality of life of this population.